2016
DOI: 10.1208/s12249-016-0490-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of Polyvinyl Alcohol as a Solubility Enhancing Polymer for Poorly Water-Soluble Drug Delivery (Part 2)

Abstract: Abstract. The KinetiSol® Dispersing (KSD) technology has enabled the investigation into the use of polyvinyl alcohol (PVAL) as a concentration enhancing polymer for amorphous solid dispersions. Our previous study revealed that the 88% hydrolyzed grade of PVAL was optimal for itraconazole (ITZ) amorphous compositions with regard to solid-state properties, non-sink dissolution performance, and bioavailability enhancement. The current study investigates the influence of molecular weight for the 88% hydrolyzed gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 47 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…Recently, reports on a novel processing technology based on temperature and high shear force mixing have shown potential in overcoming the limitations associated with conventional hot-melt extrusion and spray-drying techniques ( 143 , 147 , 151 ). More uncommon preparation methods which are not widely used and established industrially for the preparation of amorphous formulations such as supercritical fluid impregnation /solvent-antisolvent ( 84 , 92 , 102 , 149 ), electrospinning /electrospraying ( 72 , 91 , 141 , 153 , 174 ), confined impinging jet ( 107 ) and pressurized gyration ( 161 ) have also been explored even though the applicability in large scale is still a question.…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, reports on a novel processing technology based on temperature and high shear force mixing have shown potential in overcoming the limitations associated with conventional hot-melt extrusion and spray-drying techniques ( 143 , 147 , 151 ). More uncommon preparation methods which are not widely used and established industrially for the preparation of amorphous formulations such as supercritical fluid impregnation /solvent-antisolvent ( 84 , 92 , 102 , 149 ), electrospinning /electrospraying ( 72 , 91 , 141 , 153 , 174 ), confined impinging jet ( 107 ) and pressurized gyration ( 161 ) have also been explored even though the applicability in large scale is still a question.…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…The temperatures ranged from 2°C to 60°C and the relative humidity varied between 0% and 100%. The duration also varied significantly, with stability studies lasting from 24 h to two years ( 73 , 74 , 81 , 82 , 84 , 86 , 88 , 92 , 93 , 104 , 105 , 109 , 110 , 113 , 115 , 116 , 118 , 120 , 123 , 124 , 126 , 127 , 129 , 130 , 132 , 134 , 135 , 139 , 143 , 146 , 149 , 153 , 158 , 166 , 169 , 172 , 175 , 176 ). While most of the studies did not mention the container used for the physical stability test, a few specified, for example, whether a closed or open container was used ( 88 , 92 , 113 , 123 , 132 , 146 ).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…Although not specifically formulated for 3D printing, several other investigators used PVA as the matrix for the solid dispersion of drugs and observed variable miscibility between drugs and polymer by DSC and powder X-ray diffraction (PXRD) analyses. 28,[40][41][42] Thus, it is apparent that the method of preparation and the drug-polymer miscibility are important aspects of using PVA for 3D printing.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, grades 4-88, 5-88, 8-88, and 18-88 were evaluated by dissolution testing with PVA 4-88 having the best supersaturation properties of the 4 grades analyzed. Drug load dissolution studies showed that drug supersaturation was decreased with increasing drug load (61). These studies demonstrated both the feasibility of processing amorphous solid dispersions containing PVA and the positive benefit for drug supersaturation with PVA 4-88.…”
Section: Polyvinyl Alcoholmentioning
confidence: 74%